Migrant Networks and Job Search Outcomes: Evidence from Displaced Workers - Tommaso Colussi (Institute for the Study of Labor (IZA), 2015)
This paper investigates how immigrants' job search outcomes are affected by the labor market outcomes of workers from the same country of origin they are connected to. Connections are identified based on having worked for the same firm in the past. Using matched employer-employee micro data from Italy and an instrumental variables approach, I show that an increase in the employment prospects of socially connected workers improves immigrants job search outcomes. The analysis of post-displacement outcomes sheds light on the different mechanisms generating the social effect.
Keywords: J61; J63; 330; migration; job displacements; networks